2022
DOI: 10.1186/s12871-022-01706-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of head-elevated position on tracheal intubation using a McGrath MAC videolaryngoscope in patients with a simulated difficult airway: a prospective randomized crossover study

Abstract: Background The head-elevated laryngoscopy position has been described to be optimal for intubation, particularly in obese patients and those with anticipated difficult airways. Horizontal alignment of the external auditory meatus and sternal notch (AM-S) can be used as endpoints for optimal positioning. Thus, we aligned the head-elevated position with the AM-S in the horizontal plane and evaluated its effect on laryngeal visualization and ease of intubation using a McGrath MAC videolaryngoscope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…The height of the operating theatre (OT) table in our study was set at the xiphisternum of the performer, which could have also contributed to the lower CL grade as described in a study by Lee et al . [ 11 ] This study reported how table height influenced laryngeal views and anaesthesiologist comfort. The authors found that the operating table level at the xiphisternum provided better laryngeal views and anaesthesiologist comfort; hence, we decided to adopt this height in our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The height of the operating theatre (OT) table in our study was set at the xiphisternum of the performer, which could have also contributed to the lower CL grade as described in a study by Lee et al . [ 11 ] This study reported how table height influenced laryngeal views and anaesthesiologist comfort. The authors found that the operating table level at the xiphisternum provided better laryngeal views and anaesthesiologist comfort; hence, we decided to adopt this height in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Since our study recruited only patients with easy airways, that is, those with a normal BMI, mouth opening of more than 3 cm, Mallampati grades 1 and 2, normal neck movements and positive upper lip bite test, it is uncertain whether the findings can be applied to laryngoscopy and intubation in difficult airways. Even though research suggests that even in simulated difficult airways, the percentage of glottic opening and the CL grade are improved with backup HELP,[ 11 ] future prospective research can be designed to evaluate the posture and effectiveness between the two positions in anticipated difficult airways, like obese or restricted neck movements.…”
Section: Discussionmentioning
confidence: 99%
“…Among studies considered for our review but not meeting inclusion criteria, additional terms that were used include ‘sitting’,2 ‘semirecumbent’3 and ‘non-standard’ 4. Studies that have been published since we finished our literature search have continued to use variable terms 5–7…”
mentioning
confidence: 99%